Villar-Argáiz, Pilar, ed. Literary Visions of Multicultural Ireland: The Immigrant in Contemporary Irish Literature - Eufrausino, Caroline Moreira (ABEI Journal, 2014)
Villar-Argáiz, Pilar, ed. Literary Visions of Multicultural Ireland: The Immigrant in Contemporary Irish Literature. Manchester: Manchester UP, 2014. 273 pp.